2022
DOI: 10.3390/d14121111
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput DNA Metabarcoding as an Approach for Ichthyoplankton Survey in Oujiang River Estuary, China

Abstract: High-throughput DNA metabarcoding of mitochondrial 12S rRNA and Cyt b gene sequences was coupled with a morphology-based identification tool to assess ichthyoplankton community structure in Oujiang River Estuary, China. The performances of 12S and Cyt b barcoding markers were compared in terms of taxonomic resolution, detection and coverage, and their suitability was established for use as a quick and powerful ichthyoplankton assessment tool. A total of 30,138 ichthyoplankton (2462 eggs and 27,676 larvae) samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Minibarcode markers for the 12S gene have been developed and applied to environmental DNA metabarcoding studies (Milan et al., 2020; Miya et al., 2020; Sales et al., 2021) and, more recently, to ichthyoplankton studies as well (Jiang et al., 2022; Van Nynatten et al., 2023). One of the main concerns when using these markers is the conserved nature of the gene, which can impact their ability to differentiate closely related species, especially in diverse regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minibarcode markers for the 12S gene have been developed and applied to environmental DNA metabarcoding studies (Milan et al., 2020; Miya et al., 2020; Sales et al., 2021) and, more recently, to ichthyoplankton studies as well (Jiang et al., 2022; Van Nynatten et al., 2023). One of the main concerns when using these markers is the conserved nature of the gene, which can impact their ability to differentiate closely related species, especially in diverse regions.…”
Section: Discussionmentioning
confidence: 99%
“…Minibarcode markers for the 12S gene have been developed and applied to environmental DNA metabarcoding studies (Milan et al, 2020;Miya et al, 2020;Sales et al, 2021) and, more recently, to ichthyoplankton studies as well (Jiang et al, 2022;Van Nynatten et al, 2023). One of the main concerns when using (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…DNA metabarcoding is a suitable tool for the analysis and monitoring of large scale pooled samples, as it is capable of generating and detecting millions of DNA reads, thus allowing simultaneous species identification and analysis [34]. In addition, compared with traditional biological monitoring methods, uncaught fish can be found in traditional monitoring with high sensitivity, and can be used for rare and endangered species or invasive species research or early warning [56,57].…”
Section: Edna Methods Can Be Used As the First Choice For Long-term M...mentioning
confidence: 99%
“…The fastq_filter module was used to control the quality of the splicing sequence. The cluster_size module was used to cluster high-quality sequences at 97% similarity level [34]. The OTUs were then classified with NCBI GenBank database via BLAST [35].…”
Section: High Throughput Sequencing and Bioinformatics Analysismentioning
confidence: 99%
“…One study included in this Special Issue [32] used metabarcoding of bulk samples to assess the species composition of ichthyoplankton in the Oujiang River estuary in China. The authors compared the performance of 12S and cytb as metabarcoding markers and found that 12S consistently performed better, both in terms of species coverage and detection rates.…”
mentioning
confidence: 99%